The Influence of Psychological Capital on Employees Turnover Intention: A Conceptual Model - Zhang, Hui; Long, Choi Sang (Business Management and Strategy, 2024)
In the context of fierce talent competition, attracting and retaining high-performance employees is a common challenge faced by organizations. Therefore, how to utilize various resources to control employee turnover is an urgent issue at the organizational level. Psychological capital is a relatively new type of capital that has emerged after studying economic capital, human capital, and social capital. It has become a valuable and reasonable investment and has expanded to the fields of human resource management and organizational behavior, receiving widespread respect from scholars. This paper further deepens the research on the development of psychological capital in the field of human resource management through a comprehensive literature review and proposes a link between psychological capital and employee turnover intention. The results of this study show that there is a significant relationship between psychological capital and employee turnover intention. The proposed conceptual framework will make valuable contributions to future research.